May Measurement Month 2019: an analysis of blood pressure screening results from Malaysia. (20th May 2021) - Chia, Yook Chin; Devaraj, Navin Kumar; Chook, Jack Bee; Chew, Ming Tsuey; Ooi, Pei Boon; Mohamed, Mohazmi; Draman, Nani; Ng, Wei Leik; Gani, Abdul Hafiz Mohamad; Thiagarajan, Nagammai; Zulghaffar, Zafferina; Beaney, Thomas; et al.
Abstract: Despite hypertension remaining the leading cause of death worldwide, awareness of hypertension and its control rate is still suboptimal in Malaysia. This study aims to determine the proportion of both diagnosed and undiagnosed hypertension, awareness and its control rate during the yearly May Measurement Month (MMM) campaign that has been coordinated by the International Society of Hypertension. Participants aged ≥18 years were recruited at various screening sites namely universities, health facilities, shopping malls, and other sites. Participant's socio-demographic, environmental, and lifestyle data were captured using a questionnaire. Three blood pressure (BP) readings as well as anthropometric measurements were obtained from all participants. The mean of the second and third BP readings was used in analyses. Hypertension was defined as a systolic BP ≥140 mmHg and/or diastolic BP ≥90 mmHg or taking antihypertensive medication. A total of 3062 participants were recruited. The proportion with hypertension in our study was 18.7% ( n = 572). The proportion who were aware of their BP status was 63.2%. More than half (57.2%) of the hypertensives were on antihypertensive medication and 70.3% of those treated were controlled. In conclusion, in this BP screening campaign, one in five were hypertensive with almost two thirds aware of their hypertensive status. BP control among those who are taking medications was high at 70% but under 60% of hypertensives were on treatment. Hypertension screening programmes are important to promote awareness and control of hypertension as well as to reduce the devastating complications associated with this disorder.